The kombucha from Rhizophora mucronata Lam. herbal tea: Characteristics and the potential as an antidiabetic beverage - Hardoko; Evi K. Harisman; Yunita E. Puspitasari (GarVal Editorial Ltda., 2020)
Context: Kombucha from tea is reported to be beneficial for health. Moreover, it can be used as a hepatoprotective, antiproliferative, antimicrobial, antidiabetic, and antilipidemic agent and is capable of healing stomach ulcers. But kombucha from other herbal has not been studied, including kombucha from the mangrove (Rhizophora mucronata) fruit. Aims: To evaluate the characteristics and the antidiabetic potential of kombucha herbal tea from R. mucronata fruit based on in vitro, chemistry, and physical analysis. Methods: This study was conducted by an experimental method using R. mucronata herbal tea as a kombucha drink with different sugar concentrations (10, 20, 30%) and fermentation time (7, 14, 21 days) with three replications on each experiment. The analyzed parameters were the inhibition of the α-glucosidase enzyme for antidiabetic activity, total phenolics, total acids, and organoleptic characteristics. Results: The sugar concentration and fermentation time significantly affected the characteristics of the produced kombucha in inhibiting α-glucosidase. The optimum treatment in inhibition was at 10% sugar concentration and 14 days of fermentation time with IC50 of 33.95 ppm. The kombucha from R. mucronata fruit had a pH of 3.11 and contained a total phenolics of 19,679.82 mg GAE/100g, 0.52% of total acids, and was quite preferred by panelists. Conclusions: Kombucha herbal tea of R. mucronata fruit has the potential as an antidiabetic drink with a lower IC50 value than acarbose drug and commercial kombucha tea.